The Relevance of Islamic Banks in the Indonesian Economy: Responding to the Controversy About Interest and Profit Sharing - Hidayatullah, Syarif (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Islamic banks have an increasingly important role in the Indonesian economy, by offering an alternative financial system based on sharia principles, especially in terms of avoidance of riba (interest) and the implementation of a profit-sharing system. However, there is controversy among the public regarding the difference between interest and profit sharing that is often misinterpreted. This study aims to explore the relevance of Islamic banks in the Indonesian economy and respond to controversies related to the interest and profit sharing system. Using a qualitative approach, this study collects data through literature studies, case studies on several Islamic banks, and interviews with Islamic bank practitioners, Islamic economists, and Islamic bank customers. The results show that although Islamic banks have tried to explain the difference in principle between interest and profit sharing, there is still confusion among the public. Many customers consider the profit-sharing system to be similar to interest, especially since they involve the sharing of profits from economic transactions. Therefore, more intensive education and socialization are needed to reduce this misperception and increase public understanding of the excellence and transparency of the Islamic banking system.